Tracing childhood : bioarchaeological investigations of early lives in antiquity - Thompson, Jennifer L.; Alfonso-Durruty, Marta P.; Crandall, John J. (Bioarchaeological interpretations of the human past., 2014)
Bioarchaeological studies of children have, until recently, centered on population data-driven topics like mortality rates and growth and morbidity patterns. This volume examines emerging issues in childhood studies, looking at historic and prehistoric contexts and framing questions about the nature and quality of children's lives. How did they develop their social identity? Were they economic actors in early civilizations? Does their health reflect the larger community? Comparing and contrasting field research from a variety of sites across Europe and the Americas, the contributors to this.